The Effect of Enterprise Systems Implementation on the Firm Information Environment1. (14th May 2013) - Dorantes, Carlos‐Alberto; Li, Chan; Peters, Gary F.; Richardson, Vernon J.
Abstract : This study uses an archival research design to assess the impact of enterprise systems on a firm's internal information environment as reflected in the production of management earnings forecasts. Specifically, the authors hypothesize that, if enterprise systems improve management's access to decision‐relevant internal information, higher quality management earnings forecasts should ensue. Consistent with disclosure theory and the purported technical characteristics of enterprise systems, the authors find a positive association between enterprise system implementations and subsequent increases in the likelihood of management forecast issuance and the accuracy of the forecasts. Additional robustness tests support the argument that improvements in management forecasts are due to improvements in the firm's internal information environment rather than to enhancements in management's ability to manage earnings. Beyond accumulating financial reporting information, the authors note that such systems provide management with information to make day‐to‐day operational decisions. Moreover, the paper provides a basis for considering management forecast qualities as a measurable proxy for improvements in the firm's internal information environment that result from information technology investments.